Application of Freundlich and Langmuir models to multistage purification process to remove heavy metal ions by using Schizomeris leibleinii - Özer, A; Özer, D; Ekiz, HI (Elsevier Sci Ltd, 1999)
The adsorption of iron(III), lead(II) and cadmium(II) ions onto Schizomeris leibleinii, a green alga, was studied with respect to initial pH, temperature, initial metal ion and biomass concentration to determine the optimum adsorption conditions. Optimum initial pH for iron(III), lead(II) and cadmium(II) ions were 2.5, 4.5 and 5.0 at optimum temperature 30 degrees C, respectively. The initial adsorption rates increased with increasing initial iron(III), lead(II) and cadmium(II) ion concentrations up to 100, 100 and 150 mg l(-1), respectively. The Freundlich and Langmuir adsorption isotherms were developed at various initial pH and temperature values. The adsorption of these metal ions to S. leibleinii was investigated in a two-stage mixed batch reactor. The residual metal ion concentrations (C-eq) at equilibrium at each stage for a given 'quantity of dried algae (X-0)/volume of solution containing heavy metal ion (V-0)' ratio were calculated using Freundlich and Langmuir isotherm constants. The experimental biosorption equilibrium data for iron(III), lead(II) and cadmium(II) ions were in good agreement with those calculated by both Freundlich and Langmuir models. The adsorbed iron(III), lead(II) and cadmium(II) ion concentrations increased with increasing X-0/V-0 ratios while the adsorbed metal quantities per unit mass of dried algae decreased. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Schizomeris leibleinii; multistage purification process; biosorption; isotherm